The Abundance of Toxic Dinoflagellate Gambierdiscus sp, Ostereopsis sp and Prorocentrum sp on Seagrass Leaf Thalassia sp from the Nirwana Beach West Sumatera Province - Rawati Irmaida Sitorus; Thamrin '; Syafruddin Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Dinoflagellate is a group of monocelullar microalga prossesing of double flagel. This organism can be found in a subtropic and also in a tropic marine water. Some potentially toxic epibentic dinoflagellate assemblage with macroalgae and potentially to cause blooming such as Gambierdiscus sp, Ostereopsis sp and Prorocentrum sp. Blooming of this population can generate "Red Tide". This reaserch was aimed to understand about dinoflagellate abundance of Gambierdiscus sp, Ostereopsis sp and Prorocentrum sp at Nirwana Beach, West Sumatera. The method used was a survey method. Sampling was done by cutting the seagrass stands, and from the stand taken three leaves and then stored in plastic bags containing clean sea waters. The dinoflagellates were separated from seagrass leaves by shaking in a plastic bags. And then filtered with 135μm and 20 μm respectively. Dinoflagellate then observed on a Sedgewick Rafter Cell under a microscope. The results showed that the highest abundance of dinoflagellate on Thalassia sp found at station 1 (132 cell/g leaf). The lowest abundance occurred at station 3 (69 cell/g leaf), which close to mangrove area. The most abundance of all species was Prorocentrum sp, while the lowest abundance cell was Gambierdiscus sp.Key word: Dinoflagellate, Abundance, Seagrass, West Sumatera